Plant Growth and Nitrogen Flow in an Aquaponics System Integrating Lettuce Hydroponics and Loach Aquaculture - Shimakawa, Y.; Kitaya, Yoshiaki; Shibuya, T.; Endo, R. (Discoveries in Agriculture and Food Sciences, 2024)
There is an urgent need to develop production technology that uses water and other material resources effectively to create a stable food supply. Aquaponics combining hydroponics and aquaculture is expected as an efficient system for producing crops and animal proteins sustaining the reuse of water and balance of nutrient elements between both cultures, using dissolved elements in fish excrement for plant growth. To evaluate the possibility of aquaponics combining lettuce hydroponics and loach aquaculture, we analyzed the growth performances of lettuce and loach and the balance of nutrient elements, especially for nitrogen between input and output of the whole system and nitrogen flow in the system. As a result, lettuce grew in aquaponics with half strength standard solution as well as hydroponics with a standard solution by the optimal combination of the number of plants and fish. In nitrogen balance, almost 70% of nitrogen from the feed was used by growing lettuce and about 25% of nitrogen from the feed was accumulated in loach.